The Application of the Principle of Good Faith in Business Contracts: A Civil Law Perspective - Asiroht Can Sauli Sibarani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This research aims to analyze how the principle of good faith is applied in the making of business contracts, from its interpretation to its effectiveness from a civil law perspective. This research will analyze two main issues of this study, namely how the principle of good faith is recognized and applied in the formation, execution, and interpretation of business contracts, and how its application in the context of business contracts helps promote the creation of justice and legal certainty in the contracts made. This research demonstrates the role of the principle good faith based of the principle of utmost good faith or uberrimae fidei, which enhances trust and fairness the parties and reduces the occurrence of disputes between the parties during the contract period and prioritize legal certainty. Therefore, this research suggests the application of the principle of good faith as the main principle in the formation and execution of business contracts. The principle of good faith can serf as a benchmark for the wether of the contract is feasible or not to be executed